The China fantasy how our leaders explain away Chinese repression - Mann, Jim, 1946-; Mann, Jim . (New York : Viking, 2007)
""Journalist and China expert Mann examines the evolution of American policy toward China and asks, Does it make sense? What are our ideas and hidden assumptions about China? In this vigorous look at China's political evolution and its future, Mann explores two scenarios popular among the policy elite. The Soothing Scenario contends that the spread of capitalism will gradually bring about a development of democratic institutions and a progressive human rights policy. In the Upheaval Scenario, the contradictions between rich and poor, between cities and the countryside, and between the openness of the economy and the unyielding Leninist system will eventually lead to a revolution, chaos, or collapse. Against this backdrop, Mann poses a third scenario: What will happen if Chinese capitalism continues to evolve and expand but the government fails to liberalize? He explores this alternate possibility and offers a startling vision of our future with China."--From publisher description."--From source other than the Library of Congress.
Includes bibliographical references (p. [115]-120) and index.
All age.
Keywords: China -- Politics and government -- 2002-